Efektivitas Kolaborasi Sekolah Dan Orang Tua Dalam Edukasi Pencegahan Gagal Ginjal Pada Anak Di SMP Negeri 02 Blora - Rahmah, Amelia Habibatur; Astuti, Nita Yuli (JURNAL PENDIDIKAN KESEHATAN, 2025)
Kidney failure in children is a serious health issue that can have long-term impacts on their quality of life and the well-being of their families. Preventing this condition requires integrated education involving schools as formal educational institutions and parents as primary educators at home. This study aims to analyze the effectiveness of the collaboration between schools and parents in educating children about kidney failure prevention at SMP Negeri 02 Blora. The research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to 20 teachers and 50 parents. The results indicate that teachers have a relatively high level of knowledge about kidney failure prevention, whereas parents' knowledge varies, with 40% demonstrating inadequate understanding. Collaborative programs such as health seminars and healthy lifestyle campaigns were deemed effective in raising awareness among teachers and parents and fostering behavioral changes in students. However, the study also identified several challenges, including parents' time constraints, limited comprehension due to varying educational backgrounds, and communication difficulties between schools and parents. To enhance collaboration effectiveness, it is recommended to utilize digital educational media for greater flexibility, simplify educational materials to be more inclusive, and strengthen coordination between schools and parents. These findings highlight the importance of synergy between schools and families in fostering healthy lifestyles among children to prevent kidney failure. With improved management, this collaborative model can be replicated in other educational institutions to support children's health comprehensively.